Assessment of Inhalation Technique in Clinical and Functional Control of Asthma and Chronic Obstructive Pulmonary Disease - Maricoto, Tiago (2015)
Introduction: Chronic obstructive pulmonary disease and asthma affect almost 300 million individuals. Inhaled therapy is often associated with technical errors reducing efficacy and compliance.Objective: To evaluate the inhalation technique and its relation with clinical and functional control in asthma and chronic obstructive pulmonary disease.Material and Methods: Analytical cross-sectional study including patients with asthma and chronic obstructive pulmonary disease treated with any type of inhaler device. Demographic data and inquiry about previous teaching of inhalation technique were collected in all participants. Inhalation technique was evaluated in: Step 1 - device activation; Step 2 - previous expiration; Step 3 - inspiration; Step 4 - end inspiratory pause. Clinical control was assessed from the questionnaires Asthma Control Test, Control of Allergic Rhinitis and Asthma Test, modified Medical Research Council and Chronic Obstructive Pulmonary Disease Assessment Test. Spirometric evaluation was performed in all participants.Results: From a total of 62 subjects, 74.19% made at least one error, mainly during step 2 (53.2%). Previous education on inhalation technique was associated with lower number of errors (p = 0.014). There was no association between number of errors and age (p = 0.321), years of diagnosis (p = 0.119) or spirometric evaluation (p > 0.05). In asthma an association was found between number of errors and Asthma Control Test (p = 0.032) and Control of Allergic Rhinitis and Asthma Test (p = 0.008).Discussion and Conclusion: Teaching inhalation technique has a positive impact on its future performance. Most patients make mistakes, affecting clinical control in asthma, although in chronic obstructive pulmonary isease no relation was found. This is an ongoing work that aims to reevaluate inhalation technique after patients’ education and its further impact.